Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Ways to Achieve The Dimensions of Sustainable Development at The Yemeni University of Saada and its Importance; From The Point of View of Academic Leaders and Faculty Working in it Mr. Abdul Rahman Muhammad Dahesh, Co-Prof. Abdul-Jabbar Al-Tayyib Amin 2. The reality of the practice of digital citizenship by secondary school leaders in Riyadh and the requirements for its activation in the light of the European experience from their point of view Mrs. Afaf Othman Al-Ghamdi, Co-Prof. Hessa Saad Al-Arifi 3. Transforming traditional universities in The Kingdom of Saudi Arabia into smart universities in the light of employing artificial intelligence Mrs. Rehab Saud Maghrabi 4. The Degree Of the First three Grades Teachers Practice Of the Twenty-First Century Skills From Their Perspectives Mrs. Sawsan Ramzi Abdullah Abu Hilal, Co-Prof. Othman Nasser Mansour 5. Anticipating the Future of Green Human Resource Management in Riyadh’s Governmental Middle Schools Using the Delphi Method Mrs. Fatmah Hameed Altowairqi 6. Building the motivations towards E-Shopping Scale among Umm Al-Qura University students Mrs. Tahani Qablan Al-Omayri 7. The Application of Institutional Excellence Standards in Bethlehem’s Private Schools Based on Malcolm Baldrige’s Model Mrs. Shireen Elias Awad, Prof. Mahmoud A. Abu Samra